Human health risks of PAHs in soil and vegetables from Tiga, Kano State, Nigeria - Enyojo S. Okwute; Zakari Mohammed; David E. Arthur; Haruna B. Wayar; Joseph C. Akan (Toxicology Reports)
This study evaluates the concentrations of seventeen polycyclic aromatic hydrocarbons (PAHs) in soil and selected vegetable samples (onions, tomatoes, hot peppers, sweet peppers, and garden eggs) from Tiga agricultural locations in Kano State, Nigeria. Soil samples were collected from ten plots (depth profiles of 0–10 cm, 10–20 cm, and 20–30 cm) and combined at each depth to create composite samples. Additionally, 20 g of each vegetable were collected and divided into fruit, stem, and root components. Standard procedures were used for the extraction and clean-up of PAHs from both soil and vegetable samples, and instrumental analysis was conducted using SHIMADZU GC-MS (GC-17A). PAH levels in soil ranged from 1.20E-02 mg/kg to 3.80E-02 mg/kg, while vegetables showed concentrations from 1.00E-03 mg/kg to 8.90E-02 mg/kg. The 0–10 cm soil samples displayed higher PAH concentrations among all the depths studied, while the vegetables with the highest PAH concentration followed the trend: Onions > Sweet Pepper > Tomatoes > Hot Pepper > Garden Egg. Overall, total PAH concentrations in vegetables exceeded those in soil. Estimated daily PAH doses were below the Tolerable Daily Dose Limit set by FAO, indicating low health risks. Incremental lifetime cancer risk values also fell below US EPA acceptable levels (10E-06), suggesting negligible cancer risk while the hazard index was less than 1, implying no appreciable non-cancer health risks. PAH pollution was attributed to both petrogenic and pyrogenic sources. The findings of this study indicate that under the assessed conditions, the five vegetables evaluated from Tiga pose no significant risk and are considered safe for consumption.